ANALISIS SALURAN SEKUNDER TERHADAP KEBUTUHAN PETANI DI BENDUNG JANGKOK KECAMATAN NARMADA KABUPATEN LOMBOK BARAT - DOMINGGUS JAPA AMBU; BAGUS WIDHI DHARMA S.; I GUSTI NGURAH OCTOVA S. (LPPM PSDKU Kampus Mataram UNMAS Denpasar, 2021)
The purpose of the study was to determine the available discharge to irrigate the rice fields and to calculate the dimensions of the irrigation channels needed. The research method used is the Irrigation Planning Criteria issued by the Ministry of Public Works of the Republic of Indonesia as the basis for placing the dimensions of irrigation canals. The first step in writing this thesis is the Hydrological Analysis of Rainfall.The results of the analysis with the 4 initial alternatives to the planned cropping pattern obtained that the net water requirement in the fields (NFR) was 0.877 lt/sec/ha and the irrigation water requirement (DR) was 1.581 lt/sec/ha which occurred in mid-April, and obtained the dimensions of the canal. primary and secondary trapezoidal shapes in the Montang Irrigation Area, respectively, are for the width of the channel bottom (b) 2.0 m, the water depth in the channel (h) 1.5 m with a guard height of 0.5 m